The Role of the Sub-district Head in Realizing Good Governance in the Cikeusik Sub-district Government, Pandeglang Regency - Sugiyatno Sugiyatno; Widyanani Widyanani; Sri Mulyani (ijd-demos, 2025)
This study examines the role of the Sub-district Head (*Camat*) in realizing Good Governance within village-level administration and explores forms of synergy with stakeholders in Cikeusik Sub-district. The research addresses the following questions: how the Sub-district Head—as the head of the local administration—fulfills the role of realizing good governance; what options are selected to achieve this; and what forms of synergy are established. A qualitative research approach was employed, utilizing data collection methods such as interviews, documentation review, and observation. The study uses Good Governance theory as its analytical framework. The findings indicate that: 1) The Sub-district Head holds roles, duties, and authority regarding the management, guidance, and regulation of sub-district administration; consequently, the Head bears responsibility for realizing good governance in Cikeusik Sub-district through village community participation, transparency regarding performance, and full accountability in their role as the head of administration; and 2) The Sub-district Head must also be capable of fostering synergy with village-level stakeholders. This is evidenced by collaborative efforts with the village community in development projects, such as the construction of irrigation channels. It is concluded that the current Sub-district Head of Cikeusik is actively attempting to implement Good Governance principles within the sub-district administration, evidenced by improved services and administrative processes under their leadership, as well as the synergy established within the bureaucratic environment. Keywords: Sub-district Head (*Camat*), Good Governance, Government, Sub-district